The Strategy of Private Madrasah Tsanawiyah in Responding to Educational Challenges - Noor, Triana Rosalina (Al-Hayat: Journal of Islamic Education, 2024)
The research aims to analyze the strategies of private Islamic madrasah tsanawyah in responding to both external and internal educational challenges. Through qualitative research-case study at MTs. Hidayatul Muta'alimin Sidoarjo, data were collected by interviews, observations, and document studies. The research subjects were the foundation supervisor and the principal of the madrasah, who were selected purposefully. Data analysis proceeded through stages of data condensation, data display, conclusion drawing, triangulation of subjects, methods, and time as checks on data validity. The results indicate the external challenges faced by MTs. Hidayatul Muta'alimin includes economic, political, information technology, and socio-cultural challenges. The economic strategy adopted is adjusting to the community's purchasing power through affordable costs for quality education. In political and information technology conditions, the madrasah has improved the quality and competence of human resources. In response to socio-cultural challenges, the madrasah accommodates student diversity by providing non-discriminatory best services. The madrasah also addresses internal challenges such as educational funding, infrastructure, graduate competencies, and sustainable education in addressing educational funding by strengthening business units and optimizing assistance and grants. For infrastructure challenges, the madrasah has gradually improved and fulfilled educational infrastructure according to government standards. Regarding graduate competencies, the madrasah designs student soft skills programs and Islamic character formation. For sustainable education, the Madrasah foundation managers establish and organize secondary Madrasah education to accommodate junior high school graduates.